The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ani9050258
|View full text |Cite
|
Sign up to set email alerts
|

Replacing Fish Meal with Defatted Insect Meal (Yellow Mealworm Tenebrio molitor) Improves the Growth and Immunity of Pacific White Shrimp (Litopenaeus vannamei)

Abstract: Recently, ecological and economic issues have affected fish meal (FM) supply, the main source of protein for shrimp. This triggered a search for alternative dietary protein sources for shrimp production. We studied the consequences of replacing FM with a defatted insect meal, ŸnMealTM (YM), comprised of yellow mealworm (Tenebrio molitor). Growth and immune parameters of juvenile Pacific white shrimp (Litopenaeus vannanmei) were compared after an eight-week feeding trial. Shrimp were kept in aquaria with densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 61 publications
(89 reference statements)
3
67
0
Order By: Relevance
“…In the last two decades, studies on insect application in fish nutrition have continuously developed in terms of experimental data for new species, forms, and technologies of preparation of insect-derived feed materials (Tschirner et al, 2017;Gasco et al, 2019c). Insects were tested in the diet of farmed fish (Józefiak et al, 2019a;Józefiak et al, 2019b), ornamental species (Vargas-Abúndez et al, 2019), laboratory fish models (Vargas et al, 2018) as well as aquatic invertebrates (Motte et al, 2019). They are part of feeding practice in ornamental (James, 2019) fish feeding, as well as other aquatic and semiaquatic pets (Rawski et al 2018).…”
Section: Fishmentioning
confidence: 99%
“…In the last two decades, studies on insect application in fish nutrition have continuously developed in terms of experimental data for new species, forms, and technologies of preparation of insect-derived feed materials (Tschirner et al, 2017;Gasco et al, 2019c). Insects were tested in the diet of farmed fish (Józefiak et al, 2019a;Józefiak et al, 2019b), ornamental species (Vargas-Abúndez et al, 2019), laboratory fish models (Vargas et al, 2018) as well as aquatic invertebrates (Motte et al, 2019). They are part of feeding practice in ornamental (James, 2019) fish feeding, as well as other aquatic and semiaquatic pets (Rawski et al 2018).…”
Section: Fishmentioning
confidence: 99%
“…To our knowledge, no study has been done so far on the effects of dietary HI on crustaceans or fish resistance to diseases. In Pacific white shrimps, L. vannamei, 10-20% dietary TM replacing 50-100% of FM drastically reduced Vibrio parahaemolyticusinduced mortality, from 45 to 13-16% (Motte et al, 2019). Very low dietary doses of SWP, or silkrose purified from SWP, greatly increased the survival of prawns subjected to an immersion challenge with Vibrio penaecida, from 0% for control diet-fed prawns to 73-77 and 90-100% for SWPand silkrose-fed prawns, respectively (Ali et al, 2018).…”
Section: Fish and Crustaceansmentioning
confidence: 99%
“…However, few studies have investigated the effects of insects on the crustaceans and fish immune system (Table 7, 8 and 9). In crustaceans, dietary TM significantly increased both the total hemocyte counts and phenoloxidase activity of the Pacific white shrimp, Litopenaeus vannamei (Motte et al, 2019), and dietary HI increased lysozyme, total haemocyte counts and cytokine expression in the intestine of crayfish marron (C. cainii) (Foysal et al, 2019). In fish, only two studies have shown no effect of dietary insects on the immune system of fish (Mikołajczak et al, 2020;Wang et al, 2019).…”
Section: Fish and Crustaceansmentioning
confidence: 99%
“…Likewise, dried super-TM have also been effectively used to replace 50% of FM in white shrimp diets, without adverse effects on growth [ 31 ]. Motte, et al [ 71 ] also found that defatted TM larvae could potentially substitute 50% of FM in white shrimp diets, without impacts on the survival rate among all groups compared with controls.…”
Section: Dietary Inclusion T Molitor With Possmentioning
confidence: 99%
“…Recently, Motte, et al [ 71 ] reported a significant increase in the FBW, WG, and average daily gain (ADG) with the best FCR in white shrimp fed diets with 50% of FM replaced with defatted TM larvae. The authors also noticed that the FI and PER were not considerably affected among TM and FM groups.…”
Section: Effects Of Dietary Supplementation With T Molimentioning
confidence: 99%